Syndicated loans - The legal risks arising from the information memorandum - Persson,Josefin (2010)
An international syndicated loan consists of a collection of two or more separate loans made by individual banks to one borrower, which are governed by a single agreement and subject to the same terms and conditions. The arrangement, which may involve everything from just a few to hundreds of banks and enormous amounts of money, offers many advantages for borrowers since it may allow for a more flexible, easy, less expensive and less time-consuming method of raising funds. Furthermore, the syndications market provides opportunities for lenders to diversify their portfolios and to avoid the infringement of regulations on capital adequacy. A typical syndication process is initiated by the borrower who mandates a lead bank to arrange the transaction. To advertise the arrangement and to make other banks participate, the lead bank will, in conjunction with the borrower, prepare and distribute an information memorandum containing details about the borrower and the transaction. Hence, the memorandum is a marketing document of great importance and if the information provided therein later proves to be false, misleading or inaccurate and the lenders consequently suffers a loss, the question of who can be held liable for its contents may arise. Three main actors can be identified as the ones potentially liable for the lenders’ shortfall: the borrower, professional advisers and the lead bank. However, normally such inadequacy will not come to light until the loan already has gone bad. In such case, the participating banks may be tempted to sue the lead bank as the only pocket left to pay. Under English law, liability for the lead bank regarding inaccuracies in the information memorandum may be based on common law or statutory law. There are three potential heads of liability under common law of tort: fraudulent misrepresentation, negligent misrepresentation and fiduciary obligations. Under statutory law, the Misrepresentation Act may impose liability. Under Swedish law, the rules laid down under the Tort Liability Act will be decisive. In order to mitigate the lead bank’s risk of being held liable for inaccuracies in the information memorandum, disclaimer notices and exclusion clauses are included in the memorandum and the loan agreement. Such clauses ought to protect the lead bank as long as they are considered reasonable under the English Unfair Contract Terms Act or the Swedish general clause, section 36 in the Contract Act. As is accounted for in this thesis, if the borrower fails to repay the loan and it can be shown that the lead bank has performed its task negligently, a potential threat of claims for damages exists under both English and Swedish law. However, the actors in the market of syndications almost exclusively consist of sophisticated commercial parties, dealing with each other at arm’s length. Therefore, as long as no special circumstances indicate differently, disclaimers and exclusion clauses aiming at deducting liability in negligence will be effective.
Keywords: Bankrätt